Implementasi Pemberian Dana Hibah Covid 19 Bagi Pelaku Pariwisata Hotel dan Restoran di Kabupaten Badung Tahun 2020 (CITIZEN CHARTER, 2022)
The Decree (SK) of the Badung Regent Number 67/054/HK/2020 concerning the Designation of Hotels and Restaurants to Receive Tourism Grants for the 2020 Fiscal Year is the basis for the community to obtain grant funds from the government. This study aims (1) to analyze the implementation of the Covid-19 grant fund in Badung Regency (2) to analyze the factors that influence the implementation of the Covif-19 grant. The results of the research on Covid-19 grant funds in Badung Regency are that several very important inputs are needed, such as (1) the Quality and Quantity of Human Resources implementing the Covid-19 Grant Fund Distribution needs to be selected who are competent. Recommendation: Transparency and equity carried out by the Tourism Office and the Creative Economy Agency in the Provision of Covid-19 Grants to Hotel and Restaurant Tourism Actors in Badung Regency Keywords: Implementation, Grants, Community